The impact of alcohol consumption on the relationship between depression and chronic diarrhea: a cross-sectional study analysis on NHANES (2005-2010) - Wang, Yongsen; Li, Xiaotong; Cao, Zhiqun; Zhou, Yongkun (Frontiers in Psychiatry, 2024)
BACKGROUND: Alcohol consumption, depression, and chronic diarrhea are all public health issues of concern, with irreversible consequences for individual health and significant economic burdens on health care systems. Previous studies have shown that depression increases the risk of developing chronic diarrhea, but few studies have explored whether alcohol consumption has an effect on the relationship between depression and chronic diarrhea.To explore the effect of alcohol consumption on the relationship between depression and chronic diarrhea.METHODS: 12,538 adults (≥20 years) in NHANES from 2005-2010 were analyzed.Participants were stratified according to drinking status, and differences between the risk of depression and chronic diarrhea among participants who drank alcohol or not were assessed using multiple regression analysis and likelihood ratio tests.In this cross sectional, after adding possible confounders, the prevalence of depression with chronic diarrhea was higher in the drinking population than in the non-drinking population (OR,2.34, 95%CI:1.84-2.98 and 1.26, 95%CI:0.85-1.86), with a likelihood ratio test of P=0.024.Our findings suggest that there is a significant association between depression and chronic diarrhea and that alcohol consumption may increase the correlation between depression and chronic diarrhea. However, these findings require further prospective studies to provide more evidence.